Methods for calculating the magnetic field of rotating charge distribution with spherical symmetry - Beisenov, B.; Boshkayev, K.A.; Brisheva, Z.N.; Zhami, B.A.; Kalymova, Z.A.; Kuanyshbayuly, E.; Urazalina, A.A. (Recent Contributions to Physics, 2019)
The paper considers the methods for finding the magnetic field of a rotating and uniformly charged sphere. Special attention is drawn to the relatively new so-called March method, which can be used for a wide class of problems. This method makes it easy to find solutions for problems with complex conditions. Here the method is applied for a simple spherically symmetric case, the solutions of which are known. All calculations are shown in detail, with a full analysis of analytical calculations. A comparison is made with the known methods for finding the magnetic field for rotating charged spheres. It is shown how using the Marsh method one can construct force lines of the magnetic field in “Wolfram Mathematica” package. The work pursues pedagogical goals and is dedicated to students, undergraduates, Ph.D. students and young specialists of higher educational institutions in the specialties of physics, nuclear physics and astronomy.